Education Management Information System and Digital Transformation - Ibrohim, Maulana Malik; Hidayati, Dian (JUPE : Jurnal Pendidikan Mandala, 2023)
In this paper, the idea of education management information systems and how they relate to digital transformation will be discussed. It is very important for educational institutions to develop a management information system (MIS). Important to implement as far as administrative needs and people's needs demand, administrative data frameworks provide precise and ideal data that are expected to work with direction and critical thinking that empowers the implementation of arrangements, controls and functional capabilities to actually run. Qualitative descriptive methods are used in scientific writing. The study shows that the development and management of an organization's driver's license can effectively and efficiently result in decisions that are not only quick and accurate but also in line with organizational best practices. Data has become an important asset for keeping an eye on associations today. Literature review is used in this research method. The results in this paper find that essential contemplation and dynamic methodology in instructive authority are excellent and fit the hypothesis.